CoS2 / Co (OH) F heterostructure self-supporting electrolytic water oxygen evolution catalyst and application thereof

By designing CoS2/Co(OH)F heterostructure in electrolytic hydroxylase catalyst, the problems of slow kinetic rate and high thermodynamic energy barrier of the existing catalyst are solved, and high efficiency oxygen evolution and long-term stability are achieved, which is suitable for industrial high current density applications.

CN119776889AActive Publication Date: 2025-04-08JINAN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411872243.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing electrolytic oxygen-excited catalysts have problems with slow kinetic rate and high thermodynamic energy barrier, which seriously restricts their industrial application.

Method used

By designing and synthesizing a CoS2/Co(OH)F heterostructure self-supported electrolytic oxygen-induced catalyst, a one-step hydrothermal method is used to prepare defect-rich catalysts, forming heterointerfaces to regulate the length of active edge states and electron interactions, exposing more catalytic active sites.

Benefits of technology

The catalytic activity and long-term stability of the catalyst are improved, the effect of high-efficiency oxygen analysis at high current density is achieved, and the excellent full water dissolution performance is shown in alkaline membrane electrolytic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776889A_ABST
    Figure CN119776889A_ABST
Patent Text Reader

Abstract

The invention discloses a CoS2 / Co (OH) F heterostructure self-supporting electrolytic water oxygen evolution catalyst and application thereof.The catalyst is prepared through the following steps that pretreated foam cobalt, a sulfur source aqueous solution and a fluorine source aqueous solution are transferred into a high-pressure reaction container, the high-pressure reaction container is sealed and then subjected to a hydrothermal reaction, and after the reaction is finished, the catalyst is obtained; after the high-pressure reaction kettle is naturally cooled, reactants are taken out and washed and dried, and the CoS2 / Co (OH) F heterostructure self-supporting electrolysis water oxygen evolution catalyst is obtained and can be applied to alkaline electrolysis water oxygen evolution and industrial large-current-density oxygen evolution in an alkaline membrane electrode electrolysis water system. The composite material can be prepared only by a one-step hydrothermal method, is simple in test steps, can be used for oxygen evolution of alkaline electrolytic water and under high current density, has long-time stability, and can also be applied to full water decomposition in alkaline membrane electrolytic bath devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water decomposition electrocatalysts, and in particular relates to a CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst and application thereof. Background Art

[0002] Energy depletion and environmental pollution have become global problems that need to be solved urgently. The development of eco-friendly green energy is crucial to the sustainable development of human society. Compared with traditional fossil fuels, hydrogen energy has a series of advantages such as zero emissions, high efficiency and renewability, and plays an important role in promoting the realization of carbon peak and carbon neutrality strategies. Hydrogen energy has become one of the most ideal energy sources at present due to its environmental friendliness, high calorific value and recyclable production. The use of renewable energy to drive water electrolysis to produce hydrogen is expected to alleviate environmental pollution and energy shortage problems. Among them, my country's hydrogen production methods include 1) fossil fuel hydrogen production, 2) coal gasification hydrogen production, 3) biomass hydrogen production and 4) water electrolysis hydrogen production. At present, the main method of hydrogen production in the world is still fossil energy hydrogen production, which has low cost, large output and can be produced on a large scale industrially, but all rely on fossil fuels, have low energy efficiency, serious environmental pollution during hydrogen production, and the produced hydrogen needs to be purified. Water electrolysis hydrogen production is a green, environmentally friendly, clean and high-purity hydrogen production method that directly decomposes water to produce hydrogen and oxygen under the action of direct current, but it consumes too much electricity and is not economical, so its development is greatly restricted.

[0003] The oxygen evolution reaction (OER) in the four-electron transfer process at the anode has problems such as slow kinetic rate and high thermodynamic energy barrier, which seriously restricts its industrial application. Compared with the two-electron process HER, OER involves a multi-step proton-coupled electron cooperative transfer process (PCET), and the high thermodynamic energy barrier is the main bottleneck restricting the energy efficiency and industrial application of water electrolysis.

[0004] Therefore, the development of efficient and inexpensive oxygen evolution catalysts remains a key scientific issue that needs to be urgently addressed in the process of promoting the industrial application of water electrolysis technology. Currently, precious metal catalysts (Ru, Ir, etc.) and their derivatives have been considered to be the most effective catalysts for oxygen evolution in water electrolysis, but their low reserves and high prices have hindered their large-scale commercial application. Transition metal cobalt sulfides are a promising alternative to precious metal catalysts due to their abundant resources, wide range of applications, and structural diversity.

[0005] Among them, pyrite-type CoS2 is one of the many cobalt sulfides with good conductivity and excellent catalytic activity. It is an economical and effective catalyst for electrolytic water evolution that can replace precious metals. In order to further improve the intrinsic activity of cobalt-based sulfides, the method of constructing heterogeneous structures can be used to improve the electrocatalytic reaction kinetics of the electrode. Among them, the heterogeneous hybrid structure catalyst is composed of two or more components with different properties and functions. A common strategy is to composite the catalytic active phase with a conductive support material to construct an integrated electrocatalyst. This integrated structure can avoid the use of binders in the catalytic process, improve the electron transfer efficiency, increase the activity of the catalytic site, and achieve electrocatalytic water decomposition at a high current density, thereby reducing the reaction energy consumption. By forming a heterogeneous interface, the catalyst can induce charge redistribution and electron transfer at the interface, thereby regulating the reaction path and enhancing the reaction rate. In the catalytic process, cobalt-based sulfide plays a pre-catalytic role, and its surface will be oxidized to oxide / hydroxide, as a real catalytic active substance, and the reconstructed metal oxide / hydroxide nanostructure has a higher surface area, and its performance is better than that of directly synthesized metal oxide / hydroxide, and it can show higher activity in OER. By constructing heterogeneous structures, the electronic structure of active sites on the catalyst surface is optimized, the formation of reconstructed species is promoted, and the catalytic activity of the catalyst is thereby improved.

[0006] Therefore, the present invention intends to design and synthesize a unique integrated CoS2 / Co(OH)F heterostructure with a large number of defects, introduce a heterointerface into the CoS2 structure, adjust the active edge state length and electronic interaction of the heterostructure, expose more catalytic active sites and strong electronic interactions, promote the water dissociation kinetics and reconstruction process, and enhance its catalytic activity and long-term stability, which is of great significance to meet the actual needs of efficient oxygen evolution at high current density. Summary of the invention

[0007] The object of the present invention is to provide a CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst in view of the deficiencies in the prior art.

[0008] The present invention also aims to provide the application of the above-mentioned CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst in alkaline water electrolysis oxygen evolution and in alkaline membrane electrode (MEA) water electrolysis system to achieve industrial high current density oxygen evolution.

[0009] The first object of the present invention can be achieved by the following technical solution: A CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst is prepared by a method comprising the following steps:

[0010] (1) Using cobalt foam (CF) as a conductive substrate and cobalt source and performing pretreatment;

[0011] (2) transferring the pretreated cobalt foam, sulfur source aqueous solution and fluorine source aqueous solution into a high-pressure reaction vessel, sealing the high-pressure reaction vessel and performing a hydrothermal reaction. After the reaction is completed, the high-pressure reactor is cooled naturally, the reactants are taken out, washed and dried, and a CoS2 / Co(OH)F heterostructure self-supporting electrolytic water oxygen evolution catalyst grown in situ on the cobalt foam is obtained.

[0012] Heterointerface construction can modify the electronic state of the material itself and the coordination environment around the atoms, which can fundamentally improve the inherent activity of the active sites, promote the adsorption and dissociation activation reaction process of the material to water in the solution, reduce the reaction energy barrier, accelerate the catalyst reconstruction process and reaction kinetics, and thus improve the electrocatalytic performance.

[0013] The present invention successfully prepares a defect-rich CoS2 / Co(OH)F heterostructure by a one-step hydrothermal method, which can not only enhance charge transfer, but also improve the activity of catalytic sites. The catalyst carrier in the integrated structure can regulate the binding energy of the reaction intermediates by changing the electronic structure of the active site or directly participating in the reaction. By forming a heterogeneous interface, the catalyst can form defects at the interface, triggering S, F, and Co charge redistribution and electron transfer, inducing CoS2 / Co(OH)F lattice distortion, thereby regulating the reaction path and enhancing the reaction rate, exposing a large number of active sites, and enabling the material to have excellent electrocatalytic oxygen evolution performance under alkaline conditions and full water decomposition performance in alkaline membrane water electrolysis devices.

[0014] In the above-mentioned CoS2 / Co(OH)F heterostructure self-supporting water splitting electrocatalyst:

[0015] Preferably, the pretreatment in step (1) comprises first ultrasonically cleaning the foamed cobalt with acetone to remove surface organic matter, then ultrasonically cleaning the foamed cobalt with dilute hydrochloric acid to remove surface oxides, then rinsing the surface residues with deionized water and anhydrous ethanol, and finally drying the foamed cobalt in a vacuum drying oven.

[0016] More preferably, the pretreatment in step (1) comprises: firstly ultrasonically cleaning the foamed cobalt with acetone for 10 minutes to remove surface organic matter, then ultrasonically cleaning the foamed cobalt with 3 mol / L dilute hydrochloric acid for 10 minutes to remove surface oxides, then rinsing the surface residues with deionized water and anhydrous ethanol, and finally drying the foamed cobalt at 60° C. in a vacuum drying oven for 6 hours.

[0017] Preferably, the sulfur source aqueous solution in step (2) is a thiourea aqueous solution, and the concentration of the thiourea aqueous solution is 5 mmol / L to 100 mmol / L.

[0018] More preferably, the sulfur source aqueous solution in step (2) is a thiourea aqueous solution, and the concentration of the thiourea aqueous solution is 5 mmol / L to 50 mmol / L.

[0019] Preferably, the fluorine source aqueous solution in step (2) is an ammonium fluoride aqueous solution, and the concentration of the ammonium fluoride aqueous solution is 2 mmol / L to 20 mmol / L.

[0020] More preferably, the fluorine source aqueous solution in step (2) is an ammonium fluoride aqueous solution, and the concentration of the ammonium fluoride aqueous solution is 2 mmol / L to 10 mmol / L.

[0021] Preferably, during the hydrothermal reaction in step (2), the hydrothermal reaction temperature is 100 to 180° C., and the hydrothermal reaction time is 2 to 20 h; more preferably, the hydrothermal reaction time is 2 to 10 h.

[0022] Preferably, in step (2), the reactants are washed with deionized water and ethanol, and then dried under vacuum.

[0023] The above-mentioned second object of the present invention can be achieved by the following technical scheme: application of the above-mentioned CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst in alkaline water electrolysis oxygen evolution.

[0024] The present invention also provides the use of the above-mentioned CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst in an alkaline membrane electrode water electrolysis system to achieve industrial high current density oxygen evolution.

[0025] The industrial maximum current density range is preferably 0.5A / cm 2 ~1.5A / cm 2 .

[0026] Therefore, the CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst of the present invention can be prepared by a one-step hydrothermal method, and the experimental steps are simple. The prepared product can be used for alkaline water electrolysis oxygen evolution and high current density, and has long-term stability, and can also be used in alkaline membrane electrolyzer devices to achieve high current density water decomposition.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) The CoS2 / Co(OH)F prepared in the present invention is an integrated catalyst, in which the foamed cobalt (CF) not only serves as a substrate for stabilizing the heterostructure, but also serves as a sacrificial cobalt source, thereby avoiding the use of external Co cations, effectively promoting the contact between the substrate and the active sites, and without the aid of a polymer binder. It can also effectively promote the rapid diffusion of bubbles and ions and the rapid transfer of electrons, thereby accelerating the reaction process;

[0029] (2) The present invention adopts a method of constructing a heterogeneous interface to change the electronic structure and atomic arrangement of the CoS2 / Co(OH)F material, optimize the adsorption free energy of water at the active site, and reduce the reaction energy barrier; under the synergistic effect of CoS2, Co(OH)F and CF (foamed cobalt), the overall catalytic activity of the catalyst is improved;

[0030] (3) The integrated CoS2 / Co(OH)F water electrolysis catalyst of the present invention can realize efficient oxygen evolution at industrial high current density and water electrolysis in alkaline membrane electrolyzer devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings;

[0032] Figure 1 The SEM image of the CoS2 / Co(OH)F integrated water electrolysis anode oxygen evolution catalyst prepared in Example 1 is shown;

[0033] Figure 2 The TEM image of the CoS2 / Co(OH)F integrated water electrolysis anode oxygen evolution catalyst prepared in Example 1 is shown;

[0034] Figure 3 The HRTEM image of the CoS2 / Co(OH)F integrated water electrolysis anode oxygen evolution catalyst prepared in Example 1 is shown;

[0035] Figure 4 The Raman graphs of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are shown;

[0036] Figure 5 The oxygen evolution polarization curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown;

[0037] Figure 6 The graph of oxygen evolution performance of the anode of water electrolysis under industrial conditions and high current density of Example 1 is shown;

[0038] Figure 7 The long-term stability diagram of oxygen evolution at the anode of electrolyzed water in Example 1 is shown;

[0039] Figure 8 The performance diagram of Example 1 in an industrial alkaline membrane water electrolysis device is shown;

[0040] Fig. 9 The figure shows the medium- and long-term stability of the alkaline membrane water electrolysis device of Example 1. DETAILED DESCRIPTION

[0041] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0042] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0043] Unless otherwise specified, the experimental methods used in the following implementation methods are all conventional experimental methods.

[0044] Unless otherwise specified, the terms used in the following implementation methods and examples generally have the meanings commonly understood by those of ordinary skill in the art.

[0045] Part I: CoS2 / Co(OH)F heterostructure self-supported catalyst for oxygen evolution in water electrolysis

[0046] Example 1

[0047] The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst provided in this embodiment is prepared by a method comprising the following steps:

[0048] (1) Foam cobalt pretreatment:

[0049] A piece of commercially available cobalt foam (1×3 cm 2 ) was immersed in an acetone solution for 10 min, and then in a 3 mol / L hydrochloric acid solution for 10 min, and then the surface residues were washed with deionized water and anhydrous ethanol respectively, and then placed in a vacuum drying oven and dried at 60 ° C for 6 h;

[0050] (2) Preparation of CoS2 / Co(OH)F heterostructure self-supporting catalyst for water electrolysis and oxygen evolution

[0051] The pretreated cobalt foam was immersed in a 30 mM thiourea aqueous solution and a 10 mM ammonium fluoride aqueous solution and then transferred to a high-pressure reactor. After the reactor was sealed, it was placed in a forced air drying oven and reacted at 140°C for 5 hours. After the reaction was completed, the reactor was cooled naturally, the reactants were taken out, washed with deionized water and ethanol, and then vacuum dried to obtain a CoS2 / Co(OH)F heterostructure self-supporting water electrolysis and oxygen evolution catalyst.

[0052] Example 2

[0053] The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst provided in this embodiment is prepared by a method comprising the following steps:

[0054] (1) Foam cobalt pretreatment:

[0055] A piece of commercially available cobalt foam (1×3 cm 2 ) was immersed in an acetone solution for 10 min, and then in a 3M hydrochloric acid solution for 10 min, and then the surface residues were washed with deionized water and anhydrous ethanol respectively, and then placed in a vacuum drying oven and dried at 60 ° C for 6 h;

[0056] (2) Preparation of CoS2 / Co(OH)F heterostructure self-supporting catalyst for water electrolysis and oxygen evolution

[0057] The pretreated cobalt foam was immersed in 30mM thiourea aqueous solution and 10mM ammonium fluoride aqueous solution and then transferred to a high-pressure reactor. After the reactor was sealed, it was placed in a forced air drying oven and reacted at 140°C for 10 hours. After the reaction was completed, the reactor was cooled naturally, the reactants were taken out, washed with deionized water and ethanol, and then vacuum dried to obtain the CoS2 / Co(OH)F heterostructure self-supporting electrolytic water oxygen evolution catalyst.

[0058] Example 3

[0059] The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst provided in this embodiment is prepared by a method comprising the following steps:

[0060] (1) Foam cobalt pretreatment:

[0061] A piece of commercially available cobalt foam (1×3 cm 2 ) was immersed in an acetone solution for 10 min, and then in a 3M hydrochloric acid solution for 10 min, and then the surface residues were washed with deionized water and anhydrous ethanol respectively, and then placed in a vacuum drying oven and dried at 60 ° C for 6 h;

[0062] (2) Preparation of CoS2 / Co(OH)F heterostructure self-supporting catalyst for water electrolysis and oxygen evolution

[0063] The pretreated cobalt foam was immersed in a 30 mM thiourea aqueous solution and a 10 mM ammonium fluoride aqueous solution and then transferred to a high-pressure reactor. After the reactor was sealed, it was placed in a forced air drying oven and reacted at 180 ° C for 5 hours. After the reaction was completed, the reactor was cooled naturally, the reactants were taken out, washed with deionized water and ethanol, and then vacuum dried to obtain the CoS2 / Co(OH)F heterostructure self-supporting electrolytic water oxygen evolution catalyst.

[0064] Example 4

[0065] The difference from Example 1 is that in step (2), the concentration of the thiourea aqueous solution is 15 mmol / L, and the concentration of the ammonium fluoride aqueous solution is 5 mmol / L.

[0066] Example 5

[0067] The difference from Example 1 is that in step (2), the concentration of the thiourea aqueous solution is 45 mmol / L, and the concentration of the ammonium fluoride aqueous solution is 15 mmol / L.

[0068] Example 6

[0069] The difference from Example 1 is that in step (2), the concentration of the thiourea aqueous solution is 80 mmol / L, and the concentration of the ammonium fluoride aqueous solution is 20 mmol / L.

[0070] Comparative Example 1

[0071] Compared with Example 1, the difference is that no fluorine source aqueous solution is added in the preparation of the CoS2 / Co(OH)F electrode, and the obtained electrode is CoS2.

[0072] Comparative Example 2

[0073] Compared with Example 1, the difference is that no sulfur source aqueous solution is added during the preparation of the CoS2 / Co(OH)F electrode, and the obtained electrode is Co(OH)F.

[0074] Part II Structure and performance test of CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst

[0075] 1) SEM test was performed on CoS2 / Co(OH)F in Example 1, CoS2 in Comparative Example 1, and Co(OH)F in Comparative Example 2.

[0076] The SEM image of CoS2 / Co(OH)F in Example 1 is as follows Figure 1 As shown, the catalyst is anchored on the edge and surface of the nanosheets in the form of nanoparticles, where the originally smooth surface morphology becomes rougher and denser, forming a CoS2 / Co(OH)F heterointerface, which can not only enhance charge transfer, but also expose more active sites, which is beneficial to improving the catalytic efficiency.

[0077] 2) TEM test of CoS2 / Co(OH)F in Example 1

[0078] The TEM image of CoS2 / Co(OH)F in Example 1 is as follows Figure 2 As expected, the TEM images show the anchoring of CoS2 nanoparticles on the Co(OH)F nanosheets, which is consistent with the SEM results.

[0079] 3) HRTEM test of CoS2 / Co(OH)F in Example 1

[0080] The HRTEM image of CoS2 / Co(OH)F in Example 1 is as follows: Figure 3As shown, the lattice fringes with a spacing of 0.488 nm belong to the (010) plane of the crystallographic Co(OH)F, while the lattice fringes with a lattice spacing of 0.248 nm belong to the (012) plane of the CoS2 crystal, thus verifying that the material is a heterogeneous interface composed of Co(OH)F and CoS2.

[0081] 4) Raman test of CoS2 / Co(OH)F in Example 1, CoS2 in Comparative Example 1, and Co(OH)F in Comparative Example 2

[0082] The Raman pattern of CoS2 / Co(OH)F in Example 1 is as follows: Figure 4 As shown, between 200 and 800 cm -1 The wavelength range shows a group of 286, 334 and 396cm -1 The characteristic signals at 478, 517 and 685 cm -1 The characteristic peaks of CoS2 / Co(OH)F correspond to the characteristic peaks of Co(OH)F. Compared with the peaks in Co(OH)F, these peaks in CoS2 / Co(OH)F are slightly negatively shifted, suggesting that there is a strong electronic interaction between CoS2 and Co(OH)F.

[0083] 5) Testing the water splitting electrocatalytic performance of Examples 1-3 and Comparative Examples 1-2

[0084] The electrochemical performance test adopts the standard three-electrode system of CHI 760E electrochemical workstation. The specific test of water splitting electrocatalytic performance is as follows:

[0085] The polarization curve (LSV) was tested in 1M KOH solution with Hg / HgO as the reference electrode, a carbon rod as the counter electrode, and the working electrode being the sample prepared in the example or the comparative example, and the test scan rate was 5mV / s.

[0086] The oxygen evolution polarization curves of CoS2 / Co(OH)F in Example 1, CoS2 in Comparative Example 1 and Co(OH)F in Comparative Example 2 are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that when the oxygen evolution current density is 100mA / cm 2 and 200mA / cm 2 When , the overpotentials of CoS2 / Co(OH)F are 318mV and 339mV, the overpotentials of CoS2 are 342mV and 368mV, and the overpotentials of Co(OH)F are 398mV and 419mV.

[0087] The oxygen evolution performance of the CoS2 / Co(OH)F catalyst in Example 1 under industrial conditions and high current density is shown in the figure Figure 6As shown by Figure 6 It can be seen that the CoS2 / Co(OH)F catalyst can drive an industrial-grade current density of 0.5 A / cm at a relatively small overpotential of 374 mV and 412 mV. 2 and 1A / cm 2 The OER activity exceeds that of commercial RuO2 on CF, indicating its potential practical application in the field of hydrogen production by water electrolysis. The industrial-grade current density is generally referred to as >200 mA / cm 2 .

[0088] The long-term stability of oxygen evolution of CoS2 / Co(OH)F in Example 1 is shown in FIG. Figure 7 As shown by Figure 7 It can be seen that the CoS2 / Co(OH)F electrode material exhibits OER catalytic stability for at least 50 h in alkaline electrolyte.

[0089] The water decomposition performance of the CoS2 / Co(OH)F alkaline membrane electrolyzer in Example 1 is shown in FIG. Figure 8 As shown. An anion exchange membrane water electrolyzer was assembled using CoS2 / Co(OH)F as the anode and a commercial Pt / C electrocatalyst supported on a gas diffusion layer (carbon cloth) as the cathode. In an industrial water electrolysis system, the operating temperature is usually about 50-80°C to further reduce the total voltage required for water decomposition. Figure 8 It can be seen that under the condition of 80℃ for industrial water electrolysis, the CoS2 / Co(OH)F electrode only needs 1.57V and 1.77V to make the current density reach 100mA / cm 2 and 500mA / cm 2 . It showed excellent water splitting performance in alkaline membrane electrolyzer devices, indicating the potential application of this material in industrial water electrolysis systems.

[0090] The long-term stability of the MEA full water splitting of CoS2 / Co(OH)F in Example 1 is shown in FIG. Fig. 9 As shown by Fig. 9 It can be seen that the CoS2 / Co(OH)F electrode material exhibits catalytic stability for water decomposition in alkaline electrolyte for up to 120 h.

[0091] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst, characterized in that: Prepared by a method comprising the following steps: (1) Using cobalt foam as a conductive substrate and a cobalt source and performing pretreatment; (2) transferring the pretreated cobalt foam, sulfur source aqueous solution and fluorine source aqueous solution into a high-pressure reaction vessel, sealing the high-pressure reaction vessel and performing a hydrothermal reaction. After the reaction is completed, the high-pressure reactor is cooled naturally, the reactants are taken out, washed and dried, and a CoS2 / Co(OH)F heterostructure self-supporting electrolytic water oxygen evolution catalyst grown in situ on the cobalt foam is obtained.

2. The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to claim 1, characterized in that: The pretreatment in step (1) includes first using acetone ultrasonic cleaning to remove surface organic matter, then using dilute hydrochloric acid ultrasonic cleaning to remove surface oxides, then rinsing the surface residues with deionized water and anhydrous ethanol, and finally drying in a vacuum drying oven.

3. The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to claim 1, characterized in that: The sulfur source aqueous solution in step (2) is a thiourea aqueous solution, and the concentration of the thiourea aqueous solution is 5 mmol / L to 100 mmol / L.

4. The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to claim 1, characterized in that: The fluorine source aqueous solution in step (2) is an ammonium fluoride aqueous solution, and the concentration of the ammonium fluoride aqueous solution is 2 mmol / L to 20 mmol / L.

5. The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to claim 1, characterized in that: During the hydrothermal reaction in step (2), the hydrothermal reaction temperature is 100 to 180° C. and the hydrothermal reaction time is 2 to 20 hours.

6. The CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to claim 1, characterized in that: In step (2), the reactant is washed with deionized water and ethanol, and then vacuum dried.

7. Use of the CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to any one of claims 1 to 6 in alkaline water electrolysis oxygen evolution.

8. Application of the CoS2 / Co(OH)F heterostructure self-supporting water electrolysis oxygen evolution catalyst according to any one of claims 1 to 6 in achieving industrial high current density oxygen evolution in an alkaline membrane electrode water electrolysis system.

Citation Information

Patent Citations

  • Foam cobalt in-situ vulcanization nanoflower spherical Co4S3@Co hydrogen evolution material and method for preparing same

    CN108889314A

  • Preparation method and application of foamed nickel self-supporting fluorine-doped cobalt sulfide nano array

    CN116676627A

  • Preparation method of fluorine-doped cobalt sulfide nano-particle electrocatalyst, product of fluorine-doped cobalt sulfide nano-particle electrocatalyst and application of fluorine-doped cobalt sulfide nano-particle electrocatalyst in electrocatalytic oxidation of glucose

    CN118022782A